Tense, Aspect and Mood in Bantawa - Rai, Nirajan (Kirat Pragya किरात प्रज्ञा, 2025)
This study attempts to analyze the tense, aspect and mood (TAM) system in Bantawa, a Tibeto-Burman language spoken in the eastern hilly region. The study aims to present the form-function relation of the TAM in Bantawa from the typological-functional perspectives. The researcher has used his own knowledge of language to extract the data for the study through paradigm construction. Apart from this, a data set was prepared through manual method to draw relevant data to enrich the description and interpretation. The TAM was identified, described and interpreted from the transcriptions of the data set. The study reveals that TAM in Bantawa is primarily morphologically marked but it presents a syntactic and semantic contrasts. The morphemes can be changed based on syntactic behaviours. Moreover, TAM is similarly marked with other neighbouring Kirati languages.